Questionnaires for knee instability assessment in people with anterior cruciate ligament injury: a systematic review of original questionnaires and their translated versions - Marinho A.P.R.* (2020)
© 2018, © 2018 Informa UK Limited, trading as Taylor & Francis Group.Purpose: To verify the quality of questionnaires/scales regarding knee instability caused by anterior cruciate ligament (ACL) insufficiency and their translated versions. Materials and methods: Searches were conducted on Web of Science, Pubmed, Medline, Cinahl, and SportDiscuss. The COnsensus-based Standards for the selection of Health Measurement INstruments (COSMIN) scale was used to assess the article’s quality; and the measurement properties of each questionnaire/scale were also analysed. Results: Searches identified 7703 studies and 29 were included in this review. Nine were articles reporting the original development of a questionnaire/scale and 20 were translations. The original questionnaires/scales were written in English or French and were translated into Brazilian Portuguese, Portuguese, Dutch, Turkish, German, Korean, Italian, Arabic, Polish, French, and Chinese. The questionnaires/scales with best overall quality were the Cincinatti Knee Rating System, the International Knee Documentation Committee–Subjective Knee Form and the PPLP. The International Knee Documentation Committee had positive results for internal consistency (Cronbach’s alpha 0.89–0.92); for reliability and agreement (intraclass correlation coefficient (ICC) ranging from 0.88 to 0.99); and for construct validity (Pearson’s r ranged from 0.1 to 0.85). Conclusions: The International Knee Documentation Committee had the largest number of translated versions and it was considered the best instrument assessed. Furthermore, The International Knee Documentation Committee was considered to be easy to apply, short and accessible, thus it is the choice of several clinicians and researchers.Implications for rehabilitation Knee instability is one of the most important factors to be evaluated during rehabilitation of people with anterior cruciate ligament injury in both surgical and non-surgical approach. The use of questionnaires may provide a better overall functionality assessment of people with knee instability from ACL injury. To choose the most appropriate questionnaire, clinicians should consider their needs and should consider validated questionnaires linked with adequate psychometric properties which guarantee the original characteristics of a questionnaire and also guarantee reliable results.